Hydrogen Production: State of Technology. Issue 1 (July 2020) - Li, S; Kang, Q; Baeyens, J; Zhang, H L; Deng, Y M
Abstract: Presently, hydrogen is for ∼50% produced by steam reforming of natural gas – a process leading to significant emissions of greenhouse gas (GHG). About 30% is produced from oil/naphtha reforming and from refinery/chemical industry off-gases. The remaining capacity is covered for 18% from coal gasification, 3.9% from water electrolysis and 0.1% from other sources. In the foreseen future hydrogen economy, green hydrogen production methods will need to supply hydrogen to be used directly as fuel or to generate synthetic fuels, to produce ammonia and other fertilizers (viz. urea), to upgrade heavy oils (like oil sands), and to produce other chemicals. There are several ways to produce H2, each with limitations and potential, such as steam reforming, electrolysis, thermal and thermo-chemical water splitting, dark and photonic fermentation; gasification, and catalytic decomposition of methanol. The paper reviews the fundamentals and potential of these alternative process routes. Both thermo-chemical water splitting and fermentation are marked as having a long term but high "green" potential.